2004
DOI: 10.1097/00129804-200409000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Practice Guidelines for Outpatient Parenteral Antimicrobial Therapy

Abstract: EXECUTIVE SUMMARYThese guidelines were formulated to assist physicians and other health care professionals with various aspects of the administration of outpatient parenteral antimicrobial therapy (OPAT). Although there are many reassuring retrospective studies on the efficacy and safety of OPAT, few prospective studies have been conducted to compare the risks and outcomes for patients who receive treatment as outpatients rather than as inpatients. Because truly evidence-based studies are lacking, the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(128 citation statements)
references
References 188 publications
2
124
0
2
Order By: Relevance
“…21,22,34,43 Outpatient parenteral antibiotic therapy (OPAT) may be considered in stable patients to decrease hospital stay. 44 OPAT for IE however, may not be possible in most LMIC settings due to a high rate of complications associated with late hospital presentation, and unavailability of required medical services in the outpatient setting. None of our reviewed studies reported on the rates of OPAT.…”
Section: Medical Therapymentioning
confidence: 99%
“…21,22,34,43 Outpatient parenteral antibiotic therapy (OPAT) may be considered in stable patients to decrease hospital stay. 44 OPAT for IE however, may not be possible in most LMIC settings due to a high rate of complications associated with late hospital presentation, and unavailability of required medical services in the outpatient setting. None of our reviewed studies reported on the rates of OPAT.…”
Section: Medical Therapymentioning
confidence: 99%
“…This is an important treatment question as SAB is associated with a high cost burden on health care systems and is associated with considerable morbidity and mortality [2,4]. We used broad criteria for treatment failure, which are consistent with definitions outlined in previous studies, current BSAC (British Society for Antimicrobial Chemotherapy) best practice recommendations, and IDSA (Infectious Diseases Society of America) guidelines for OPAT [3][4][5]8]. While these criteria likely overestimated the number of treatment failures in our study, the failure rate of 35.6% was similar to previous OPAT studies evaluating patients with SAB or SAB/IE (range 13-31%) [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…OPAT (outpatient parenteral antimicrobial therapy) is frequently used to complete this treatment and has several advantages including cost savings, decreased risk of hospital-acquired infection, and increased patient autonomy [3]. While OPAT is generally considered safe and effective, recent studies have reported failure rates in patients with SAB from 13-31% suggesting opportunities for process improvement [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Contraindications to outpatient therapy include the presence of a prosthetic valve, persistently positive blood cultures, congestive cardiac failure, vegetations greater than 10 mm in length, recurrent embolic events, conduction abnormalities and Staphylococcus aureus aetiology. 15 It is, however, clear from more recent cohort reports that OPAT services are successfully treating S aureus and prosthetic valve endocarditis, [16][17][18] and recent European Society of Cardiology recommendations do not explicitly preclude this practice (Table 3). 19 It remains standard practice to initially manage endocarditis with a minimum inpatient stay of 2 weeks prior to OPAT, with the possible exception of clinically stable patients with 'oral' streptococcal infection.…”
Section: How Does Opat Normally Work In the Uk?mentioning
confidence: 99%